Crisálida: um website como proposta colaborativa de formação - Amaral, Georgia Stella Ramos do (2023)
This work is linked to the research line of Development of Networked Educational Technologies (LP1) of the Graduate Program in Networked Educational Technologies of the Federal University of Santa Maria (UFSM) and to the research group POLIFONIA - Group of Research in Policies Linguistics, Teacher Training and New Technologies for Language Teaching at the Federal University Fronteira Sul (UFFS). The theme chosen for the research was the production of authorial didactic material, with the purpose of knowing what researchers in the area are highlighting as relevant on this topic and proposing a solution. This is an exploratory, applied research with a qualitative approach. In the physical absence of the teacher or as support in their pedagogical practice, the didactic material is the means by which interaction with the student takes place. Knowing the importance of didactic material, whether in EAD, in person or in remote teaching; the importance of the teacher being the author of his own material, leaving his identity, his mark in this virtual world, in the case of digital materials; the difference it makes for teachers to take responsibility for their training; this research is justified as a collaboration proposal for the birth of this new teacher: author, autonomous and engaged, since there is still a lot of difficulty in the use of digital technologies. Since neither initial nor continuing training seem to be meeting the demand, given the size of the imbalance that is present in the area of education, we have to make use of other alternatives that can help teachers effectively and quickly. This research has the general objective of creating a website that serves as support in the formation and authorship process of Basic Education teachers; and, as specific: recognize the importance of didactic material in the teaching and learning process; check which tools teachers have had difficulties with in recent years, especially in the pandemic period; develop a strategy to help teachers achieve digital fluency; and, collaborate in encouraging the creation of authorial didactic material with the use of digital technologies. The focus of this research is informal training, the one in which the teacher seeks interest or need, that is, self-training. The product developed is a website, where the teacher will find digital content, freely accessible and in micro format, to help in the production of their own didactic material. For the creation of this product, the methodology of instructional design was used, and, as a theoretical reference, texts by Paulo Freire, Vilson Leffa, Cristóbal Cobo and John Moravec, Nelson Pretto, Andréia Inamorato dos Santos and Andrea Filatro, among others were fundamental.